ASPEK HUKUM PERBEDAAN BESAR NPOPTKP UNTUK WARIS DAN HIBAH WASIAT SERTA BUKAN WARIS DAN HIBAH WASIAT DALAM BPHTB - TRI APRIANO ALAMSYAH (PREMISE LAW JURNAL, 2017)
The different rate of NPOPTKP (Non-Taxable Purchase Value) for the same rate of NPOP (Tax Object Purchase Value) will influence the rate of NPOPKP (Taxable Purchase Value). It will then lead to different rate of BPHTB (Property Title Acquisition Duty) that has to be paid by tax payers. It will certainly bring impacts on the justice principle that has to be strongly held in tax collection. Therefore, a research was done on the rate difference of NPOPTKP in calculating the outstanding BPHTB for inheritors and grant beneficiaries; and, for non-inheritors and non-grant beneficiaries, the fulfillment of justice principle in determining the rate of NPOPTKP for inheritors and grant beneficiaries; and, for non-inheritors and non-grant beneficiaries, and on the fulfillment of legal certainty on the alleviation of outstanding BPHTB to inheritors and grant beneficiaries.Keywords: NPOPTKP (Non-Taxable Purchase Value), Inheritance and Grant, BPHTB (Property Title Acquisition Duty)